Karyotype characteristics and chromosomal polymorphism of Chironomus “annularius” sensu Strenzke (1959) (Diptera, Chironomidae) from the Caucasus region - Karmokov, Mukhamed Kh. (Comp Cytogenet, 2018)
Abstract. The study presents data on the karyotype characteristics and features of chromosomal polymorphism of Chironomus “annularius” sensu Strenzke (1959) (Diptera, Chironomidae) from three populations of the Caucasus region (South and Central Caucasus, and Eastern Ciscaucasia). We found 17 banding sequences in the Caucasian populations. We observed inversion polymorphism in almost all chromosome arms except for arm G. The genetic distances between all the studied populations of Ch. “annularius” were calculated using Nei criteria (1972). In spite of relative geographic proximity, the genetic distances between populations of the Caucasus are quite large, and they do not form a single cluster of Caucasian populations. The population of the South Caucasus goes to the European cluster, the population of the Central Caucasus goes to the Asian cluster and the population of Eastern Ciscaucasia does not belong to any of the outlined clusters. Principal component analysis (PCA) shows a similar picture. Two of the Caucasian populations do not follow Hardy-Weinberg expectation, there being a marked deficiency of heterozygotes in arms A, B and C, arguably, due to negative selection of heterozygotes or founder effect. All the obtained data are indicative of the complex genetic structure of Caucasian populations of Ch. “annularius” and total complexity microevolution processes occurring in the Caucasus region.